Genes Integral to the Reproductive Function of Male Reproductive Tissues Drive Heterogeneity in Evolutionary Rates in Japanese Quail. Issue 1 (1st January 2018) - Finseth, Findley R; Harrison, Richard G
Abstract: Early comparative genomics studies originally uncovered a nonintuitive pattern; genes involved in reproduction appeared to evolve more rapidly than other classes of genes. Currently, the emerging consensus is that genes encoding reproductive proteins evolve under variable selective pressures, producing more heterogeneous divergence patterns than previously appreciated. Here, we investigate a facet of that heterogeneity and explore the factors that drive male reproductive tissue-based heterogeneity in evolutionary rates. In Japanese quail ( Coturnix japonica ), genes with enriched expression in the testes evolve much more rapidly than those enriched in the foam gland (FG), a novel gland that secretes an airy foam that males transfer to females during mating. We compared molecular evolutionary patterns among (1) genes with induced expression in breeding vs. wintering conditions for both tissues and (2) genes that encode foam proteins (FPs) vs. those with varying degrees of expression specificity in the FG. We report two major findings. First, genes upregulated in breeding condition testes evolve exceptionally rapidly, while those induced in breeding condition FGs evolve slowly. These differences hold even after correcting for hormonally-dependent gene expression and chromosomal location. Second, genes encoding FPs are extremely conserved in terms of gene identity and sequence. Together, these finding suggest that genes involved in the reproductive function of each tissue drive the marked rate of heterogeneity.